Vices or Virtues? A reflection on the concept of Political Professionalization - Oliveira, Rui (2021)
The purpose of this article is to critically review the concept of political professionalization, looking at its operationalization, what the literature understands about the concept, the impact of Professionalization on society in general, and the implications for the Political Elites in particular. It is concluded that the process of Professionalization prepares the political class for the challenges of modernization, but leads to a removal of citizens from politics, less representation and a more closed and less varied political class, with consequences for the quality of democracies.